A Magnetic Nanocarrier of Ciprofloxacin Used for Restraining the Growth of the Multidrug-Resistant Pseudomonas aeruginosa - Kleoniki Giannousi; Eleni Zouni; Nikolaos Grigoriadis; Ioannis S. Vizirianakis; Ilias M. Oikonomou; Valeria Nicolosi; Catherine Dendrinou-Samara (Inorganics)
Ciprofloxacin (CPL) is an effective antibiotic against Pseudomonas aeruginosa. However, its use is limited by the emergence of multi-resistant strains. In this study, 8–15 nm manganese ferrite (MnFe2O4) nanoparticles, aminated and/or PEGylated, have been used as drug-delivery systems of CPL. The magnetic nanoparticles (MNPs) were prepared in the presence of the aliphatic amines octadecylamine (ODA), oleylamine (OAm), or PEG8000 to achieve the appropriate surface chemistry for the direct conjugation of CPL and drug loading into the PEG matrix, respectively. The primary MNPs proved to be biocompatible in calf thymus (CT)-DNA interaction studies, with binding constant values Kb in the range of 4.43–6.5 × 104 (g/mL)−1. ODA as a coater gave rise to MnFe2O4 MNPs, with a high percentage of free amines that further allowed for the conjugation of 90.9% CPL, which gradually released via a non-Fickian anomalous transport motif. The 25.1% CPL that loaded in the PEGylated MNPs led to a partial transformation of the nanoflowers into more aggregated forms. The release profile, although steeper, is described by the same model. The isolated magnetic nanocarrier with a high content of CPL was evaluated for its antimicrobial activity against a multi-resistant strain of P. aeruginosa using an automated industrial instrument (BacT/ALERT®3D), and its molecular profile was outlined by studying its interaction with plasmid DNA (pDNA). The prototype use of BacT/ALERT®3D allows for the simultaneous screening of multiple samples, while it foreshadows the transition to a preclinical phase.